Risk assessment of adolescent sex offenders: a case overview - Šobot, Valentina; Ivanović Kovačević, Svetlana; Knežević, Vladimir; Vejnović, Ana Marija (Engrami, 2022)
One of the most important roles of mental health professionals in the forensic evaluation of adolescent sex offenders is to assess the risk of future delinquent behavior. The psychiatric and psychological expertise of a 17-year-old male adolescent, who was accused of rape, was conducted at the court’s request in order to determine the maturity of the juvenile, the risk of reoffending, and the need for treatment. The current case report demonstrates risk assessment based on the structured professional evaluation. This approach integrates clinical with empirical knowledge and it has been proven highly useful in risk assessment of sexual recidivism in adolescent sex offenders. The assessment was based on the integration of tha data obtained from the structured risk assessment tool Juvenile Sex Offender Assessment Protocol-II (JSOAP-II, Prentky and Righthand, 2003) and data based on standard professional expertise by forensic clinicians. The aim of the present case report was to show the advantages of a structured approach to risk assessment in adolescent sex offenders, as well as to assess the practical implications related to appropriate case management and the need for treatment.